Kustaanheimo-Stiefel استخدام الحل التحليلي لمعادلات الحركة للقمر الاصطناعي في إيجاد العناصر البعدية للمدار بواسطة نظرية - مهند علي عبد الزيدي (University of Thi-Qar Journal of Science, 2019)
In this paper the analytic solution for equation of the satellite motion is used tofind the Dimension elements for the orbit represented by Semi-major axis andeccentricity, this is done by the effect of the second harmonic J ب 2 of short term orbit forthree initial conditions it is seen from it that the increasing in the eccentricity associatedwith increasing of semi major axis, which proved that the linear relationship betweenthem. These factors have been calculated using K-S theory which summarized incalculating the coefficients resulted from analytical integral for differential equationusing coefficients called K-S. Kustaanheimo-Stiefel theorem is summarized inestimation the coefficients resulted from the solution of the ordinary differential equation.The procedure is shown in two steps: firstly, the calculation of the initial conditionsaccording to their relation with the distances and velocity of the satellite. Secondly, theanalytical solution is achieved to finding these coefficients (α,β,λ,λ*(.